Scarlet ebook - Bendis, Brian Michael (Scarlet., 2022)
A young woman is pushed to the edge by a world filled by police brutality, government corruption, and unspeakable crimes. After a mysterious murder and a near-death experience, Scarlet Rue wakes from a coma with her world shattered. Fueled by rage, guilt, and her vision of a better future; she takes the fight to her oppressors . . . and anyone else who gets in her way. Striking back against the corrupt cops who tore her life apart and sparks an uprising in this all-too-real tale of power, corruption, and lies. • Complete with behind the scenes material, sketches, and design concepts from both Bendis and illustrator Alex Maleev. ""The art is gorgeous and Scarlet's voice is very well defined by her writer."" –Comicsverse